2016
DOI: 10.3945/jn.116.237644
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa Flavanol Intake and Biomarkers for Cardiometabolic Health: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Cocoa flavanols may improve cardiometabolic health. Evidence from small short-term randomized clinical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 69 publications
2
82
0
3
Order By: Relevance
“…This neutral effect of cocoa and dark chocolate on LDL-C is consistently shown in the recent metaanalysis of 19 randomized controlled trials in which chocolate or cocoa consumption did not change the LDL-C concentration. 31 Both the ALD and CHOC+ALD decreased LDL-C by a comparable degree; however, there were different treatment effects on LDL subclasses. The ALD decreased large buoyant LDL particles, whereas the CHOC+ALD decreased small dense LDL particles.…”
Section: Discussionmentioning
confidence: 91%
“…This neutral effect of cocoa and dark chocolate on LDL-C is consistently shown in the recent metaanalysis of 19 randomized controlled trials in which chocolate or cocoa consumption did not change the LDL-C concentration. 31 Both the ALD and CHOC+ALD decreased LDL-C by a comparable degree; however, there were different treatment effects on LDL subclasses. The ALD decreased large buoyant LDL particles, whereas the CHOC+ALD decreased small dense LDL particles.…”
Section: Discussionmentioning
confidence: 91%
“…Recent meta-analyses (Table S3) [138,139,140,141,142,143,144,145,146,147,148,149,150,151] suggest that the consumption of flavanol-containing tea and tea products could reduce total- and LDL-cholesterol as well as body mass index (BMI) and waist circumference (WC), while chocolate and cocoa flavanols also appear to regulate blood lipid levels. Nonetheless, the results of these analyses are inconsistent, partly due to the large heterogeneity of the clinical trials included.…”
Section: Discussionmentioning
confidence: 99%
“…Results of that study suggest that chocolate intake result in beneficial changes in liver enzymes and protect against insulin resistance (55). The results of a randomized controlled trial also support a role for cocoa flavanol intake in improving insulin resistance (48). The current data is insufficient to recommend chocolate and cocoa for glycemic control.…”
Section: Polyphenolsmentioning
confidence: 94%
“…Previous studies have failed to observe benefits of cocoa polyphenols on blood lipids in subjects with hypertension stage 1 (45), overweight (46) and in patients with heart failure (47). A recent meta-analysis of 19 randomized controlled trials of varying designs with a total of 1,131 participants indicated that cocoa flavanols were associated with reductions in total triglycerides (−0.10 mmol/L) and increases in HDL-C (0.06 mmol/L) intake (48). Recently published results from the Flaviola Health Study revealed that twicedaily ingestion of 450 mg of cocoa flavanols for 1 month decreased TC by 0.20 mmol/L and LDL-C by 0.17 mmol/L whereas HDL-C increased by 0.10 mmol/L in a low risk, primary prevention population.…”
Section: Polyphenolsmentioning
confidence: 99%